Environmental Warfare against American Citizens: An Open Letter to the Joint Chiefs of Staff - Herndon, J. Marvin; Whiteside, Mark (Advances in Social Sciences Research Journal, 2020)
While the public perception of the recent attempts to unseat duly-elected U.S. President Donald J. Trump is thought to be solely of national origin, there is strong evidence of a more pernicious, United Nations’ sanctioned environmental assault on America and on American citizens. The United States and other sovereign nations are in the midst of a highly organized, covert environmental warfare assault, underlain by deception and deceit, orchestrated by a foreign entity, and perpetrated in America by the U.S. Air Force and its contractors, and facilitated by intelligence-agency operatives. The intent, to slowly and insidiously sicken, weaken, and debilitate citizenry, cause weather and climate chaos, cripple agriculture, and devastate the environment, is so cleverly underwritten and camouflaged as to have gone unnoticed in the 2018 National Defense Strategy of the United States of America and, presumably, is unknown to the Joint Chiefs of Staff. But it is described here. American military officers have the responsibility to protect their own citizens, especially as they possess the means to destroy human and environmental health. Systematically poisoning the air Americans breathe, harming human and environmental health, causing weather and climate chaos, damaging agriculture, and deceiving the public as to the adverse human and environmental health consequences – all under secret orders originating from a foreign entity – we allege, violates not only their Oath of Office, but is tantamount to treason. The United States Air Force co-optation, deceit, and unquestioning capitulation to a foreign entity should be of grave concern to the Joint Chiefs of Staff. With due humility we must emphasize that no military asset is worth damaging human and environmental health, especially on a national or planetary-scale, and especially due to a deceptively-worded, Trojan horse, United Nations international treaty whose signatories presumably were duped into signing in the false belief that they were preventing hostile environmental warfare.